Polypropylene composite material as well as preparation method and application thereof
By combining polypropylene resin with a variety of modifiers, the problems of poor adhesion and insufficient tensile strength of polypropylene materials are solved, and the coating adhesion and tensile strength are significantly improved, which is suitable for the preparation of automotive parts .
Patent Information
- Application Number
- CN202411542814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Due to the low surface polarity and poor adhesion, polypropylene materials are difficult to spray paint or paint, and their tensile strength is insufficient, making it difficult to meet the needs of automotive parts.
The coating adhesion and stretching of polypropylene materials are significantly improved by combining polypropylene resin with SAN resin, cycloolefin polymer, hollow glass microbeads, glycidyl methacrylate grafted polypropylene and nucleating agent. strength.
The coating adhesion and tensile strength of polypropylene materials have been significantly improved, making it suitable for the preparation of automotive parts, especially automotive bumpers.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a polypropylene composite material and a preparation method and application thereof. Background Art
[0002] Polypropylene is widely used due to its low density, high cost performance, excellent heat resistance, rigidity, chemical resistance, easy processing and recycling, etc. Therefore, it is also known as the largest and fastest growing plastic variety.
[0003] After surface processing of polypropylene, it can become our common daily product. The most common surface processing technology is spraying. Since polypropylene is a non-polar crystalline material with low surface polarity and poor surface adhesion, it is difficult to spray paint or coating on parts made of it without surface pretreatment.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a polypropylene composite material and a preparation method and application thereof. The polypropylene composite material has excellent coating adhesion and tensile strength.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A polypropylene composite material comprises the following components in parts by weight: 100 parts of polypropylene resin, 14-32 parts of SAN resin, 4-21 parts of cycloolefin polymer, 9-16 parts of hollow glass microspheres, 0.08-1.1 parts of glycidyl methacrylate grafted polypropylene, and 0.04-0.32 parts of a nucleating agent.
[0008] The present invention creatively combines the above raw materials, takes polypropylene resin as the matrix, and SAN resin, cycloolefin polymer, hollow glass microspheres, PP-g-GMA and nucleating agent work together to significantly improve the coating adhesion and tensile strength of the polypropylene material. The polypropylene composite material is very suitable for preparing automobile parts, especially for preparing automobile bumpers.
[0009] The applicant speculates that in the polypropylene resin matrix system of the present invention, the addition of glycidyl methacrylate grafted polypropylene can improve the polarity of the polypropylene material of the system, effectively improve the surface polarity of polypropylene, and can also improve the compatibility of other components with the substrate, improve the migration performance of other components in the polypropylene substrate, improve the melt fluidity and formability of the melt, and effectively improve the processing performance. The epoxy group of the glycidyl methacrylate interacts with the polypropylene molecular chain to effectively improve the intermolecular force; while the polypropylene crystallizes, a large number of hydroxyl groups on the surface of the hollow glass microspheres can effectively improve the wetting of non-polar polypropylene materials during the coating process. At the same time, the hollow glass microspheres migrate in the matrix, which can improve the fluidity of cycloolefin polymers and SAN resins in the polypropylene matrix, and can promote the rapid migration of cycloolefin polymers and SAN resins to the surface of the polypropylene composite material to form a dense polar layer, and form a specific crystalline network structure from the surface to the inside in the polypropylene composite, so that it not only has a high paint film adhesion, but also has excellent tensile strength.
[0010] The amount of the SAN resin is 14 to 32 parts, for example, 14 parts, 15 parts, 16 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts or a range consisting of any two of these values.
[0011] Preferably, the amount of the SAN resin is 15 to 30 parts.
[0012] The amount of the cycloolefin polymer is 4 to 21 parts, for example, 4 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 21 parts or a range consisting of any two of these values.
[0013] Preferably, the amount of the cycloolefin polymer is 4 to 20 parts.
[0014] The amount of the hollow glass microspheres is 9 to 16 parts, for example, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts or a range consisting of any two of these values.
[0015] Preferably, the amount of the hollow glass microspheres is 10 to 15 parts.
[0016] The amount of glycidyl methacrylate grafted polypropylene is 0.08 to 1.1 parts, for example, 0.08 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.1 parts or a range consisting of any two of these values.
[0017] Preferably, the amount of glycidyl methacrylate grafted polypropylene is 0.1 to 1 part.
[0018] The amount of the nucleating agent is 0.04 to 0.32 parts, for example, 0.04 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.32 parts or a range consisting of any two of these values.
[0019] Preferably, the amount of the nucleating agent is 0.05 to 0.3 parts.
[0020] Preferably, the polypropylene composite material comprises the following components in parts by weight: 100 parts of polypropylene resin, 15 to 30 parts of SAN resin, 5 to 20 parts of cycloolefin polymer, 10 to 15 parts of hollow glass microspheres, 0.1 to 1 part of glycidyl methacrylate grafted polypropylene, and 0.05 to 0.3 part of a nucleating agent.
[0021] Preferably, the polypropylene composite material comprises the following components in parts by weight: 100 parts of polypropylene resin, 20 to 25 parts of SAN resin, 10 to 15 parts of cycloolefin polymer, 12 to 13 parts of hollow glass microspheres, 0.5 to 0.8 parts of glycidyl methacrylate grafted polypropylene, and 0.1 to 0.2 parts of nucleating agent. In particular, when the amount of each raw material is within this range, the compatibility is better, and under the joint action of each component, the coating adhesion and tensile strength are further improved.
[0022] Wherein, in the polypropylene composite material of the present invention, the weight percentage of the polypropylene resin is not less than 60%.
[0023] Preferably, in the polypropylene composite material of the present invention, the weight percentage of the polypropylene resin is 60-70%, for example, it can be 60%, 61%, 62%, 64%, 65%, 66%, 68%, 70% or a range consisting of any two values therein.
[0024] Preferably, in the polypropylene composite material of the present invention, the weight percentage of the SAN resin is not less than 10%.
[0025] Preferably, in the polypropylene composite material of the present invention, the weight percentage of the SAN resin is not less than 10-20%, for example, it can be 10%, 11%, 12%, 14%, 15%, 16%, 18%, 20% or a range consisting of any two values therein.
[0026] Preferably, the melt flow rate of the polypropylene resin at 230°C / 2.16kg is 5 to 30 g / 10min, for example, 5 g / 10min, 6 g / 10min, 8 g / 10min, 10 g / 10min, 12 g / 10min, 15 g / 10min, 18 g / 10min, 20 g / 10min, 25 g / 10min, 30 g / 10min or a range consisting of any two of these values.
[0027] It should be noted that the present invention is not limited to the source of the polypropylene resin, which can be recycled polypropylene or new material, as long as its melt flow rate is within the specified range of the present invention.
[0028] Preferably, the polypropylene is recycled polypropylene, which is derived from at least one of washing machine barrel materials, ton bag materials, and daily miscellaneous materials. The use of recycled polypropylene can realize waste utilization and turn waste into treasure, and recycled raw materials are easy to obtain and low in cost.
[0029] Preferably, the melt flow rate of the polypropylene resin at 230°C / 2.16kg is 10-18g / 10min. The present invention controls the melt flow rate of the polypropylene resin within this range, which has better fluidity and molding effect, can improve processing performance, improve molding effect, and is more conducive to the crystallization of polypropylene, promoting the formation of a crystalline network structure from the surface to the inside, thereby further improving the coating adhesion and tensile strength.
[0030] Preferably, the content of acrylonitrile in the SAN resin is 18-35wt%, for example, it can be 18wt%, 20wt%, 22wt%, 25wt%, 28wt%, 30wt%, 32wt%, 35wt% or a range consisting of any two values therein. SAN resin, also known as AS resin, is a copolymer of styrene and acrylonitrile, which has good processing fluidity and a good toughening effect. It can form a dense polar layer together with other ingredients, promote the formation of a crystalline network structure from the outside to the inside, thereby further improving the coating adhesion and tensile strength.
[0031] Preferably, the content of acrylonitrile in the SAN resin is 25-30 wt %.
[0032] The SAN resin has a melt flow rate of 1.4 to 3.3 g / 10 min at 220° C. / 5 kg according to the ISO1133-2011 method, for example, 1.4 g / 10 min, 1.5 g / 10 min, 1.8 g / 10 min, 2 g / 10 min, 2.5 g / 10 min, 3 g / 10 min, 3.3 g / 10 min or a range consisting of any two of these values.
[0033] Preferably, the true density of the hollow glass microspheres is 0.35 to 0.6 g / cm 3 , for example, it can be 0.35 g / cm 3 , 0.4g / cm 3 , 0.42g / cm 3 , 0.45g / cm 3 , 0.46g / cm 3 , 0.48g / cm 3 , 0.5g / cm 3 , 0.52g / cm 3、 0.55g / cm 3 , 0.6g / cm 3 Or a range consisting of any two values.
[0034] Preferably, the true density of the hollow glass microspheres is 0.46 to 0.50 g / cm 3 .
[0035] Preferably, the average particle size of the hollow glass microspheres is 5 to 100 μm, for example, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or a range consisting of any two of these values.
[0036] Wherein, the average particle size of the hollow glass microspheres is tested according to GB / T 19077-2016.
[0037] Preferably, the average particle size of the hollow glass microspheres is 30 to 50 μm.
[0038] Preferably, the grafting rate of glycidyl methacrylate in the glycidyl methacrylate grafted polypropylene is 0.2-1.5wt%, for example, it can be 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt% or a range consisting of any two of these values.
[0039] Preferably, the grafting rate of glycidyl methacrylate in the glycidyl methacrylate grafted polypropylene is 0.5-1wt%. By controlling the grafting rate within this range, the coating adhesion and tensile strength are further improved. If the grafting rate is too low, the improvement effect is not good. If the grafting rate is too high, it may lead to fluidity (resulting in poor processability) or affect the crystallization of polypropylene, thereby causing performance degradation.
[0040] Preferably, the nucleating agent includes at least one of an α-crystal nucleating agent and a β-crystal nucleating agent.
[0041] Preferably, the α-crystal nucleating agent includes at least one of an aromatic phosphate salt-based α-crystal nucleating agent, an organic carboxylate-based α-crystal nucleating agent, a sorbitol-based α-crystal nucleating agent, and a rosin-based α-crystal nucleating agent.
[0042] The β-crystal nucleating agent includes at least one of an inorganic oxide β-crystal nucleating agent, an inorganic salt β-crystal nucleating agent, a condensed ring aromatic hydrocarbon β-crystal nucleating agent, an organic carboxylic acid and its salt β-crystal nucleating agent, and an aromatic amide β-crystal nucleating agent.
[0043] Preferably, the cycloolefin polymer includes at least one of a cycloolefin copolymer and a cycloolefin homopolymer.
[0044] Preferably, the glass transition temperature of the cycloolefin copolymer is 78-123°C, for example, it can be 78°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 123°C or a range consisting of any two of these values.
[0045] Wherein, the glass transition temperature of the cycloolefin copolymer is tested according to the method of ISO 11357-2.
[0046] Preferably, the polypropylene composite material of the present invention may further include at least one of a toughening agent, mineral powder, a lubricant, a colorant, an antioxidant, a weathering agent, an antistatic agent, a flame retardant, and an ultraviolet light absorber.
[0047] The polypropylene composite material of the present invention may include a toughening agent, and suitable toughening agents include but are not limited to ethylene-octene copolymer, SEBS, maleic anhydride grafted POE, maleic anhydride grafted SEBS and combinations thereof.
[0048] The polypropylene composite material of the present invention may include mineral powder, and suitable mineral powder includes but is not limited to calcium carbonate, mica, kaolin, magnesium hydroxide, boehmite and combinations thereof.
[0049] The polypropylene composite material of the present invention may include a colorant. Suitable colorants include, but are not limited to, carbon black, titanium dioxide, zinc sulfide, iron red, titanium yellow and combinations thereof.
[0050] The polypropylene composite material of the present invention may include a lubricant. Suitable lubricants include, but are not limited to, polyethylene wax, fatty acid ester, hyperbranched amide and combinations thereof.
[0051] The polypropylene composite material of the present invention may include an antioxidant. Suitable antioxidants include, but are not limited to, antioxidant 1098, antioxidant 1010, antioxidant 1076, antioxidant 168 and combinations thereof.
[0052] The polypropylene composite material of the present invention may include a weathering agent, and suitable weathering agents include but are not limited to hindered amine light stabilizers, benzotriazole ultraviolet light absorbers, and combinations thereof.
[0053] The polypropylene composite material of the present invention may include an antistatic agent. Suitable antistatic agents include, but are not limited to, zinc oxide, manganese dioxide, chromium trioxide, and combinations thereof.
[0054] The polypropylene composite material described in the present invention may include a flame retardant, and suitable flame retardants include but are not limited to brominated polymers (e.g., brominated polystyrene), metal dialkyl phosphites (e.g., tris(diethylphosphite)aluminum), metal hydroxides (e.g., magnesium hydroxide), aromatic phosphates (e.g., resorcinol di(diphenyl phosphate) ester and bisphenol A di(diphenyl phosphate) ester) and combinations thereof.
[0055] The polypropylene composite material of the present invention may include a UV absorber, and suitable UV absorbers include but are not limited to hydroxybenzophenones, hydroxybenzotriazoles, hydroxybenzotriazines, cyanoacrylates, nanoscale inorganic materials (eg, titanium oxide, cerium oxide, and zinc oxide), and combinations thereof.
[0056] The present invention also provides a method for preparing a polypropylene composite material, comprising the following steps:
[0057] According to the proportion, polypropylene resin, SAN resin, cycloolefin polymer, hollow glass microspheres, glycidyl methacrylate grafted polypropylene and nucleating agent are uniformly mixed, melt-extruded and granulated to obtain a polypropylene composite material.
[0058] Preferably, the temperature of the melt extrusion is 170-210°C.
[0059] The invention also provides an application of the polypropylene composite material in the preparation of automobile parts.
[0060] The polypropylene composite material of the present invention has excellent coating adhesion and tensile strength, and is very suitable for preparing automobile parts, and is particularly suitable for preparing automobile bumpers.
[0061] The beneficial effects of the present invention are as follows: the present invention uses polypropylene resin as a matrix, and SAN resin, cycloolefin polymer, hollow glass microspheres, PP-g-GMA, and a nucleating agent work together to significantly improve the coating adhesion and tensile strength of the polypropylene material. The polypropylene composite material is very suitable for preparing automotive parts, especially for preparing automotive bumpers. DETAILED DESCRIPTION
[0062] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0063] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0064] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0065] The raw materials used in the embodiments and comparative examples are described as follows:
[0066] Polypropylene resin-1: recycled polypropylene, the base material is ton bag material, and the melt flow rate measured at 230℃ / 2.16kg is 10.0g / 10min.
[0067] Polypropylene resin-2: Recycled polypropylene, sourced from daily miscellaneous materials, with a melt flow rate of 18.0 g / 10 min measured at 230°C / 2.16 kg.
[0068] Polypropylene resin-3: Recycled polypropylene, sourced from washing machine barrel material, with a melt flow rate of 30.0 g / 10 min measured at 230°C / 2.16 kg.
[0069] Polypropylene resin-4: recycled polypropylene, sourced from daily miscellaneous materials, with a melt flow rate of 5.0 g / 10 min measured at 230°C / 2.16 kg.
[0070] Polypropylene resin-5: The melt flow rate measured at 230°C / 2.16kg is 10 g / 10 min. It is purchased from Sinopec, with the brand name PP EP300M.
[0071] SAN resin-1: The content of acrylonitrile is 30 wt%, Kumho Chemical, brand SAN 350N.
[0072] SAN resin-2: The content of acrylonitrile is 25 wt%, and the brand is SAN NF2200AE.
[0073] SAN resin-3: The content of acrylonitrile is 35 wt%, Kumho Chemical, brand SAN 350N HW.
[0074] SAN resin-4: The content of acrylonitrile is 18 wt %, Kumho Chemical, brand SAN 310TR.
[0075] PP-g-GMA-1: glycidyl methacrylate grafted polypropylene, glycidyl methacrylate grafting rate is 1%, homemade.
[0076] PP-g-GMA-2: glycidyl methacrylate grafted polypropylene, glycidyl methacrylate grafting rate is 0.5%, homemade.
[0077] PP-g-GMA-3: glycidyl methacrylate grafted polypropylene, glycidyl methacrylate grafting rate is 0.2%, homemade.
[0078] PP-g-GMA-4: glycidyl methacrylate grafted polypropylene, glycidyl methacrylate grafting rate is 1.5%, homemade.
[0079] PP-g-GMA-5: Glycidyl methacrylate grafted polypropylene, glycidyl methacrylate grafting rate is 1%, Guangzhou Dongjin Plastic Technology Co., Ltd., brand PPG-2321.
[0080] PP-g-MAH: maleic anhydride grafted polypropylene, maleic anhydride grafting rate is 1%, homemade.
[0081] Hollow glass microsphere-1: true density is 0.46g / cm 3 , Zhengzhou Shenglait Hollow Glass Microsphere New Material Co., Ltd., brand HL46.
[0082] Hollow glass microsphere-2: true density is 0.50g / cm 3 , Zhengzhou Shenglite Hollow Glass Microsphere New Material Co., Ltd., brand HL50.
[0083] Hollow glass microsphere-3: true density is 0.6g / cm 3 , Zhengzhou Shenglite Hollow Glass Microsphere New Material Co., Ltd., brand HL60.
[0084] Hollow glass microsphere-4: true density is 0.35g / cm 3 , Zhengzhou Shenglite Hollow Glass Microsphere New Material Co., Ltd., brand HL35.
[0085] Cyclic olefin polymer-1: Cyclic olefin copolymer, Japan Polyplastics, brand TOPAS 8007F-04.
[0086] Cyclic olefin polymer-2: Cyclic olefin copolymer, Zeonex 330R from Japan.
[0087] Cyclic olefin polymer-3: Cyclic olefin homopolymer, Zeonor of Japan, brand name ZEONOR 1020R.
[0088] Nucleating agent-1: Aryl phosphate ester α-crystalline nucleating agent, Shanxi Chemical Research Institute, brand TMP-6.
[0089] Nucleating agent-2: organic carboxylate α-crystal nucleating agent, produced by Melicon, brand HPN-68L.
[0090] Nucleating agent-3: Aromatic amide β-crystal nucleating agent, Shanxi Chemical Research Institute, brand TMB-5.
[0091] Talc: Tianyuan Company, brand TYT-777A.
[0092] Wherein, the preparation methods of PP-g-GMA-1 to 4 all include the following steps:
[0093] Dicumyl peroxide (1 wt% of polypropylene) is dissolved in glycidyl methacrylate, then mixed with polypropylene evenly, and then the mixture is reactively extruded through a twin-screw extruder at a screw temperature of 165-200° C. to obtain polypropylene grafted glycidyl methacrylate (PP-g-GMA).
[0094] The grafting rate of glycidyl methacrylate is controlled by controlling the ratio of glycidyl methacrylate to polypropylene, thereby obtaining PP-g-GMA-1 to 4 with different grafting rates.
[0095] The preparation method of PP-g-MAH refers to that of PP-g-GMA, except that GMA is replaced by MAH.
[0096] The testing standards for raw material parameters are as follows:
[0097] In the present invention, the melt flow rate of the polypropylene resin is measured according to ISO1133-2011 method under the condition of 230°C / 2.16kg.
[0098] In the present invention, the content of acrylonitrile in SAN resin can be measured by elemental analysis, such as using the high temperature combustion method to analyze the content of conventional organic elements in the sample, and the elements to be measured are carbon (C), hydrogen (H), and nitrogen (N). The test conditions can be selected as follows: sample weight: 2 mg, decomposition temperature: 950-1200°C, analysis time: C, H, and N are measured simultaneously for 6-9 minutes.
[0099] In the present invention, the test method for the grafting rate of glycidyl methacrylate in glycidyl methacrylate grafted polypropylene is as follows: before testing the grafting rate, the PP-g-GMA needs to be purified, 5 g of the PP-g-GMA sample is dissolved in 150 mL of hot xylene (above 110° C.), poured into 200 mL of acetone, the unreacted GMA monomer and GMA homopolymer are dissolved in acetone, and the precipitate is the purified PP-g-GMA; 1 g of the purified PP-g-GMA is dissolved in 70 mL of hot xylene (above 110° C.), 4 mL of 0.1 mol / L trichloroacetic acid xylene solution is added, and the mixture is heated at 130° C. to obtain the purified PP-g-GMA. Reflux at ~135°C for 90 min to fully open the epoxy groups on GMA, titrate with 0.05 mol / L KOH methanol solution, use phenolphthalein as an indicator, and calculate the grafting rate based on the amount of KOH methanol solution consumed. The grafting rate Gd=142.15*(V0-V)*c / (1000*m), wherein V0 is the volume (mL) of KOH-methanol solution consumed in titrating ungrafted PP, V is the volume (mL) of KOH-methanol solution consumed in titrating grafted PP, c is the molar concentration of KOH, m is the mass of PP-g-GMA titrated, and 142.15 is the molecular weight of GMA.
[0100] The density of hollow glass microspheres was tested according to the method of GB / T 21782.3-2008.
[0101] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0102] Examples 1 to 22, Comparative Examples 1 to 7
[0103] The formulations of the polypropylene composite materials of Examples 1 to 22 and Comparative Examples 1 to 7 are shown in Table 1 and Table 2 (all in the tables are parts by weight).
[0104] The preparation methods of the polypropylene composite materials of Examples 1 to 22 and Comparative Examples 1 to 7 all include the following steps:
[0105] According to the proportion, polypropylene resin, SAN resin, cycloolefin polymer, hollow glass microspheres, glycidyl methacrylate grafted polypropylene and nucleating agent are uniformly mixed, melt-extruded and granulated at 170-210° C. to obtain a polypropylene composite material.
[0106] Table 1
[0107]
[0108]
[0109] Table 2
[0110]
[0111] Performance Testing
[0112] 1. Coating adhesion
[0113] 1.1 Peel strength: The polypropylene composition prepared above was injection molded into a 100*100*2mm square plate sample, and the primer was sprayed on the square plate in sequence, baked at 80℃ for 5min, painted with color paint, baked at 80℃ for 5min, sprayed with varnish, and baked at 80℃ for 30min to obtain the coating after the material was sprayed. The tensile strength of the coating peeled off from the surface of the material was measured, and the final test result was the average of three measurements, and the unit of peel strength was N / m; the test tensile speed was 50mm / min, the peeling width was 10mm, and the peeling angle was 180°; the test temperature was 23℃.
[0114] 1.2 High-pressure water jet: refer to the method in "DIN55662-2009" for testing, angle: 90°, water temperature: 60℃, distance: 100cm, time: 60s, water flow: 11.3L / min test, compare with the standard image in "DIN55662-2009", and rate. The lower the grade, the better the coating adhesion.
[0115] 2. Tensile strength performance: Tested in accordance with ISO 527-2-2012, rate 10mm / min.
[0116] Table 3
[0117]
[0118]
[0119] It can be seen from Table 3 that the polypropylene composite material of the present invention has excellent coating adhesion and tensile strength. The water impact resistance grade of the polypropylene composite material of the present invention is ≤1, the peel strength is ≥850N / m, and the tensile strength is ≥33.6MPA.
[0120] By comparing Example 2 with Comparative Examples 1 to 7, it can be seen that the present invention uses polypropylene resin as a matrix, and the SAN resin, cycloolefin polymer, hollow glass microspheres, PP-g-GMA, and nucleating agent work together to significantly improve the coating adhesion and tensile strength of the polypropylene material. The lack of any of these raw materials or the use of other raw materials in place of them will result in a significant decrease in coating adhesion and tensile strength.
[0121] It can be seen from Examples 1, 4 and Examples 2 to 3 that the coating adhesion and tensile strength are further improved by controlling the weight of each raw material to: 100 parts of polypropylene resin, 20 to 25 parts of SAN resin, 10 to 15 parts of cycloolefin polymer, 12 to 13 parts of hollow glass microspheres, 0.5 to 0.8 parts of glycidyl methacrylate grafted polypropylene, and 0.1 to 0.2 parts of nucleating agent.
[0122] By comparing Example 2 with Examples 5 to 8, it can be seen that the present invention further improves the coating adhesion and tensile strength by controlling the melt flow rate of the polypropylene resin to 10 to 18 g / 10 min.
[0123] By comparing Example 2 with Examples 9 to 11, it can be seen that the present invention further improves the coating adhesion and tensile strength by controlling the acrylonitrile content in the SAN resin to 25 to 30 wt%.
[0124] Comparing Example 2 with Examples 12 to 14, it can be seen that the present invention controls the true density of the hollow glass microspheres to be 0.46 to 0.5 g / cm 3 , further improving the coating adhesion and tensile strength.
[0125] By comparing Example 2 with Examples 17 to 19, it can be seen that the present invention further improves the coating adhesion and tensile strength by controlling the grafting rate of GMA in PP-g-GMA to 0.5 to 1 wt%.
[0126] By comparing Example 2 with Examples 21 to 22, it can be seen that the present invention uses an α-crystal nucleating agent to further improve coating adhesion and tensile strength.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polypropylene composite material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of polypropylene resin, 14 to 32 parts of SAN resin, 4 to 21 parts of cycloolefin polymer, 9 to 16 parts of hollow glass microspheres, 0.08 to 1.1 parts of glycidyl methacrylate grafted polypropylene, and 0.04 to 0.32 parts of a nucleating agent.
2. The polypropylene composite material according to claim 1, characterized in that: The melt flow rate of the polypropylene resin at 230° C. / 2.16 kg is 5 to 30 g / 10 min, preferably 10 to 18 g / 10 min.
3. The polypropylene composite material according to claim 1, characterized in that: The content of acrylonitrile in the SAN resin is 18-35 wt %, preferably 25-30 wt %.
4. The polypropylene composite material according to claim 1, characterized in that: The true density of the hollow glass microspheres is 0.35 to 0.6 g / cm 3 , preferably 0.46 to 0.50 g / cm 3 .
5. The polypropylene composite material according to claim 1, characterized in that: The grafting rate of glycidyl methacrylate in the glycidyl methacrylate grafted polypropylene is 0.2-1.5 wt %, preferably 0.5-1 wt %.
6. The polypropylene composite material according to claim 1, characterized in that: The nucleating agent includes at least one of an α-crystal nucleating agent and a β-crystal nucleating agent.
7. The polypropylene composite material according to claim 6, characterized in that: The α-crystal nucleating agent includes at least one of an aromatic phosphate ester salt α-crystal nucleating agent, an organic carboxylate salt α-crystal nucleating agent, a sorbitol α-crystal nucleating agent, and a rosin α-crystal nucleating agent; and / or The β-crystal nucleating agent includes at least one of an inorganic oxide β-crystal nucleating agent, an inorganic salt β-crystal nucleating agent, a condensed ring aromatic hydrocarbon β-crystal nucleating agent, an organic carboxylic acid and its salt β-crystal nucleating agent, and an aromatic amide β-crystal nucleating agent.
8. The polypropylene composite material according to claim 1, characterized in that: The cycloolefin polymer includes at least one of a cycloolefin copolymer and a cycloolefin homopolymer.
9. The method for preparing the polypropylene composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the proportion, polypropylene resin, SAN resin, cycloolefin polymer, hollow glass microspheres, glycidyl methacrylate grafted polypropylene and nucleating agent are uniformly mixed, melt-extruded and granulated to obtain a polypropylene composite material.
10. Use of the polypropylene composite material according to any one of claims 1 to 8 in the preparation of automobile parts.
Citation Information
Patent Citations
Polypropylene material with high rigidity and high heat resistance and preparation method thereof, as well as injection molding product and preparation method thereof
CN108841085A
Boiling-resistant color-changing polypropylene composite material and preparation method thereof
CN111187468A
Polypropylene composite material with low dielectric constant and high weather resistance and preparation method thereof
CN113717465A
Polypropylene composition as well as preparation method and application thereof
CN116003914A
Polypropylene composition and preparation method thereof
CN117757185A